Rhodium‐Catalyzed Synthesis of 4‐Bromo‐1, 2‐dihydroisoquinolines: Access to Bromonium Ylides by the Intramolecular Reaction of a Benzyl Bromide and an α‐Imino Carbene. (2nd March 2016) - He, Jun; Shi, Yinping; Cheng, Wanli; Man, Zengming; Yang, Dongdong; Li, Chuan‐Ying
Abstract: Highly functionalized 4‐bromo‐1, 2‐dihydroisoquinolines were synthesized from readily available 4‐(2‐(bromomethyl)phenyl)‐1‐sulfonyl‐1, 2, 3‐triazoles. A bromonium ylide is proposed as the key intermediate, which can be formed by the intramolecular nucleophilic attack of the benzyl bromide on the α‐imino rhodium carbene formed in the presence of the rhodium catalyst.